(3GdJhVjM aj Md ZhGeV GdJfbjMs - (3YHO Gddg GHf eSYhO Hf JGL GdTQjYIs; (3UOQ GdTQjYI GdGUZQ , YHjOGddg Hf eSYhO Hf eMehO Hf CMeO GdeMHhHj,J (B747 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdYHO GdeJhSd Edi Gddg ef YHjOGddg GHf eSYhO s
(3BNQgG (B:s
(3dhLhO GdYUeI hGddg hdi GdYUeI s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3CUhd Gdabgs